Chronic O-GlcNAcylation and Diabetic Cardiomyopathy: The Bitterness of Glucose - Ducheix, Simon; Magré, Jocelyne; Cariou, Bertrand; Prieur, Xavier (Frontiers in Endocrinology, 2018)
Type 2 diabetes (T2D) is a major risk factor for heart failure. Diabetic cardiomyopathy (DC) is characterised by diastolic dysfunction and left ventricular hypertrophy. Epidemiological data suggest that hyperglycaemia contributes to the development of DC. Several cellular pathways have been implicated in the deleterious effects of high glucose concentrations in the heart: oxidative stress, accumulation of advanced glycation end products (AGE), and chronic hexosamine biosynthetic pathway (HBP) activation. In the present review, we focus on the effect of chronic activation of the HBP on diabetic heart function. The HBP supplies N-acetylglucosamine moiety (O-GlcNAc) that is O-linked by O-GlcNAc transferase (OGT) to proteins on serine or threonine residues. This post-translational protein modification modulates the activity of the targeted proteins. In the heart, acute activation of the HBP in response to ischaemia-reperfusion injury appears to be protective. Conversely, chronic activation of the HBP in the diabetic heart affects Ca2+ handling, contractile properties, and mitochondrial function and promotes stress signalling, such as left ventricular hypertrophy and endoplasmic reticulum stress. Many studies have shown that O-GlcNAc impairs the function of key protein targets involved in these pathways, such as phospholamban, calmodulin kinase II, troponin I and FOXO1. The data show that excessive O-GlcNAcylation is a major trigger of the glucotoxic events that affect heart function under chronic hyperglycaemia. Supporting this finding, pharmacological or genetic inhibition of the HBP in the diabetic heart improves heart function. In addition, the SGLT2 inhibitor dapagliflozin, a glucose lowering agent, has recently been shown to lower cardiac HBP in a lipodystophic T2D mice model and to concomitantly improve the diastolic dysfunction of these mice. Therefore, targeting cardiac-excessive O-GlcNAcylation or specific target proteins represents a potential therapeutic option to treat glucotoxicity in the diabetic heart.